Show that the locus of the point from which equal tangents may be drawn to the spheres $x^2 +y^2 +z^2 =1$, $x^2 + y^2 +z^2 + 2x - 2y +2z -1 = 0$ , $x^2 + y^2 +z^2 - x +4y -z - 2 = 0$ is the straight line $\frac{x - 1}{2} = \frac{y-2}{5} = \frac{z - 1}{3}$

I have tried :

Let $P(x ,y , z)$ be the point whose locus is required. Since length of the tangents to the three spheres are equal

$$ \sqrt{x^2 +y^2 +z^2 -1} = \sqrt{x^2 + y^2 +z^2 + 2x - 2y +2z -1 } = \sqrt{x^2 + y^2 +z^2 - x +4y -z - 2}$$

from the last to members,we get

$$x- y + z = 0,$$

from the last two members , we get

$$ 3x - 6y +8z +1 = 0 ,$$

from the first and last member, we get

$$x - 4y + 6z +1 = 0$$

Please tell me how to find the equation of line.

any help would be appreciated, Thank you

  • $\begingroup$ How have you found your first equation? $\endgroup$ Sep 8 '15 at 17:09
  • $\begingroup$ @Aretino From squaring the first 2. $\endgroup$
    – Guy
    Sep 8 '15 at 17:10

Notice that two equation are enough to specify a line, so for instance you could give the solution as the line given by $x-y+z=0$ and $x-4y+6z=-1$ (your first and third equation, but every other pair would do), and that would be perfectly legitimate. The other equation is a combination of these, so it is not necessary.

These can be rewritten in several different ways. For instance, you can eliminate $x$ by subtracting the second from the first one and get $3y-5z=1$, that is $3(y-2)=5(z-1)$. Similarly, you can eliminate $y$ and get $3(x-1)=2(z-1)$. These two equations are equivalent to yours and are those given by the textbook.


Rewrite the equations of the spheres: $$ x^2+y^2+z^2=1 $$ $$ (x+1)^2+(y-1)^2+(z+1)^2=4 $$ $$ \left(x-\frac{1}{2}\right)^2+(y+2)^2+\left(z-\frac{1}{2}\right)^2=\frac{13}{2} $$ So: $$ \begin{array}{ccc} \text{sphere}&\text{radius}&\text{center}\\ 1.& 1 & (0,0,0)^T\\ 2.& 2 & (-1,1,-1)^T\\ 3.& \sqrt{13/2} &(1/2,-2,1/2)^T \end{array} $$ The length of a tangent to a sphere centered at $(x,y,z)$ with radius $r$ from $(a,b,c)$ is: $$ \sqrt{(x-a)^2+(y-b)^2+(z-c)^2-r^2} $$ From here, it's not hard to finish.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.